2010
DOI: 10.1002/mc.20706
|View full text |Cite
|
Sign up to set email alerts
|

Association of IL‐1 polymorphisms and IL‐1 serum levels with susceptibility to nasopharyngeal carcinoma

Abstract: Previous studies demonstrated that the polymorphism of interleukin-1 (IL-1) produce alterations of the protein expression and may contribute to oncogenetic processes. The aim of this study was to investigate the relationship between IL-1A gene polymorphisms and NPC susceptibility and the influence of on IL-1α serum levels in cases versus controls. To test whether the genetic variants of IL-1A gene modify the risk of nasopharyngeal carcinoma (NPC), we compared the -889C/T and rs3783553 polymorphisms between 248… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 32 publications
3
37
1
Order By: Relevance
“…Recently, a novel functional polymorphism (rs3783553 TTCA/-) resident in miR-122 has been discovered, and is reported to affect the transcription of IL1A by changing the binding strength of miR-122 and miR-378 (Gao et al, 2009). The polymorphism has subsequently been reported to be related to decreased risk of HCC (Gao et al, 2009), nasopharyngeal carcinoma (Yang et al, 2011), and gastric cancer (Zeng et al, 2014). In this study, we evaluated the potential relationship between the ILIA rs3783553 insertion/deletion polymorphism and the risk of BC, and found that the ILIA rs3783553 ins/ins (ttca/ttca) genotype and the ins (ttca) allele distributions between cases and controls were significantly different.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, a novel functional polymorphism (rs3783553 TTCA/-) resident in miR-122 has been discovered, and is reported to affect the transcription of IL1A by changing the binding strength of miR-122 and miR-378 (Gao et al, 2009). The polymorphism has subsequently been reported to be related to decreased risk of HCC (Gao et al, 2009), nasopharyngeal carcinoma (Yang et al, 2011), and gastric cancer (Zeng et al, 2014). In this study, we evaluated the potential relationship between the ILIA rs3783553 insertion/deletion polymorphism and the risk of BC, and found that the ILIA rs3783553 ins/ins (ttca/ttca) genotype and the ins (ttca) allele distributions between cases and controls were significantly different.…”
Section: Discussionmentioning
confidence: 99%
“…A polymerase chain reaction (PCR) assay was used to analyze the IL1A gene rs3783553 polymorphism. Details of the primer sequences and reaction conditions have been described previously (Gao et al, 2009;Yang et al, 2011;Zeng et al, 2014). To confirm the accuracy of the genotyping, randomly selected PCR products were sequenced, and the results were verified.…”
Section: Genotypingmentioning
confidence: 99%
See 1 more Smart Citation
“…reported that the IL1A rs3783553 ins/ins homozygous genotype is associated with a significantly reduced risk of hepatocellular carcinoma. Similarly, decreased risks were found for nasopharyngeal carcinoma (Yang et al, 2011), gastric cancer (Zeng et al, 2014), cervical carcinoma , and epithelial ovarian cancer (Zhang et al, 2014b). Furthermore, patients of this genotype demonstrated a reduced risk of developing stages T3 and T4 of papillary thyroid carcinoma (Gao et al, 2014) and poor cervical carcinoma tumor differentiation .…”
Section: Discussionmentioning
confidence: 87%
“…Further analysis revealed that this insertion may disrupt binding of miR-122/miR-378 to IL1A, thereby increasing expression of interleukin-1 alpha (IL-1a; ). Subsequently, several groups have investigated the relationship between this polymorphism and hepatocellular carcinoma (Du et al, 2014;Wang et al, 2014), nasopharyngeal carcinoma (Yang et al, 2011), gastric cancer (Zeng et al, 2014), papillary thyroid carcinoma (Gao et al, 2014), cervical carcinoma (Pu et al, 2014b), and epithelial ovarian cancer (Zhang et al, 2014). However, no study to date has assessed its association with CRC risk.…”
Section: Introductionmentioning
confidence: 99%